Determination of the convective heat transfer constant (c and n) in a solar still - Dan Mugisidi; Abdul Rahman; Oktarina Heriyani; Pancatatva Hesti Gunawan (Jurnal Teknosains, 2021)
The geometry of a solar still determines the convection constants C and n, which in turn affect the convection heat transfer coefficient’s value and mass. A method for determining the value of convection heat transfer constants C and n has already been developed by the researchers. Therefore, this study aimed to use several methods and theories to find the value of convection heat transfer constants C and n. The results are then compared with the results of the study. The solar still used in this study has one slope. To reduce variables that cannot be controlled, the data collection was conducted indoors using a halogen lamp that can be regulated as a heat source for 24 hours nonstop. The sea surface height in the solar still was maintained at a height of 20 mm, using a height regulator. Temperature was measured using a data logger set to enter data every hour. The desalinised clean water was stored in bottles placed on scales that were recorded every one hour. Room temperature was maintained in the range of 35 to 36 oC. The data in this study were used to calculate the heat transfer constants C and n to obtain the value of the convection heat transfer coefficient and mass calculation. This study compares the calculation models of Tiwari, Dunkle and Power. The following calculation model results: Tiwari model, C = 0.082 and n = 0.612; Dunkle model, C = 0.075 and n = 1/3; Power model, C = 0.815 and n = 0.611. The C and n values obtained with these four approaches reveal that the results from the Power model calculation are the closest to the actual mass, showing a percentage deviation of 1.63%.